PENGARUH PEMBUBUHAN KAPORIT TERHADAP PARAMETER PH DAN AMONIA EFFLUENT PENGOLAHAN AIR LIMBAH RUMAH SAKIT - Iftihatun Nuraini; Hening Darpito (FT-USNI, 2018)
Water pollution from hospitals comes from waste water; one of the parameters that disturbs aesthetics is ammonia. Ammonia comes from the process of reforming amino acids by aerobic and anaerobic bacteria. One of the ammonia treatment is the chlorination method. The purpose of this study was to reduce the ammonia level of hospital wastewater using the chlorination method. Chlorination is used using hypochlorous acid (HOCl-) or chlorine. The chlorine dose used in the study was 2 mg / l, 4 mg / l, 6 mg / l, 8 mg / l and 10 mg / l. Data analysis using Complete Randomized Design using one way ANOVA Test. The results of research conducted on hospital ammonia wastewater showed that there was an effect of chlorine dose on ammonia levels. Chlorine dose which is quite effective in reducing ammonia levels in the study was 10 mg / l. the effectiveness of this dose can reduce ammonia by 14.08%. The test results obtained there were significant differences in the decrease in ammonia levels in each dose of chlorine with a p value of 0,000 <α = 0,005